Improving Student Engagement - Jim Parsons; Leah Taylor (Arizona State University, 2011)
This paper reviews research literature in the area of student engagement to discover curricular and pedagogical ideas educators might successfully use to better engage student learning. Student engagement has historically focused upon increasing achievement, positive behaviors, and a sense of belonging to help students remain in school. The authors suggest that work in student engagement has grown from a focus upon disengaged students (who are not learning) to engaged learners (who are learning) and theorize that older work attempted to reshape ârenegadeâ students into schooling, but current work revises schools to fit student needs.